Development and evaluation of a low cost IgG ELISA test based in RBD protein for COVID-19 - Villafañe, Luciana María (2021)
Serology tests for SARS-CoV-2 have proven to be important tools to fight against the COVID-19 pandemic. These serological tests can be used in low-income and remote areas for patient contact tracing, epidemiologic studies and vaccine efficacy evaluations. In this study, we used a semi-stable mammalian episomal expression system to produce high quantities of the receptor-binding domain-RBD of SARS-CoV-2 in a simple and very economical way. The recombinant antigen was tested in an in-house IgG ELISA for COVID-19 with a panel of human sera. A performance comparison of this serology test with a commercial test based on the full-length spike protein showed 100% of concordance between tests. Thus, this serological test can be an attractive and inexpensive option in scenarios of limited resources to face the COVID-19 pandemic.